PNPLA1 mutations cause autosomal recessive congenital ichthyosis in golden retriever dogs and humans - Grall, Anaïs; Haußer-Siller, Ingrid; Thomas, Anne; Fontaine, Jacques; Pin, Didier; Zimmermann, Robert; André, Catherine; Fischer, Judith (Nature genetics, 2012)
Ichthyoses comprise a heterogeneous group of genodermatoses characterized by abnormal desquamation over the whole body, for which the genetic causes of several human forms remain unknown. We used a spontaneous dog model in the golden retriever breed, which is affected by a lamellar ichthyosis resembling human autosomal recessive congenital ichthyoses (ARCI), to carry out a genome-wide association study. We identified a homozygous insertion-deletion (indel) mutation in PNPLA1 that leads to a premature stop codon in all affected golden retriever dogs. We subsequently found one missense and one nonsense mutation in the catalytic domain of human PNPLA1 in six individuals with ARCI from two families. Further experiments highlighted the importance of PNPLA1 in the formation of the epidermal lipid barrier. This study identifies a new gene involved in human ichthyoses and provides insights into the localization and function of this yet uncharacterized member of the PNPLA protein family.